Analisis Sentimen Media Sosial Terhadap Aplikasi Perbankan Untuk Mengetahui Kepuasan Pengguna Aplikasi: Studi Kasus Pada Livin by Mandiri dan BCA Mobile - Nurvita Trianasari; Symisius Lintang Ranataru (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In this study, the researchers aimed to explore how sentiment expressed on social media platforms towards e-servqual provided by Livin' by Mandiri and BCA Mobile applications. This research uses sentiment analysis by collecting data from Twitter. Naïve Bayes is the method chosen for this research due to its user-friendly nature and ability to handle large datasets. Regarding the results of sentiment analysis on the e-servqual dimensions for the BCA Mobile application, overall opinions tend to be negative, although there are some positive opinions, especially on the variables of user friendliness, personal nedss, and efficiency. However, sentiments towards the dimensions of site organization, responsiveness, and reliability are mostly filled with negative sentiments. In contrast, sentiments towards the Livin by Mandiri application mostly contain positive sentiments. In the e-servqual dimension, Personal Needs, user frendlines and Responsiveness, and Site Organization all show positive sentiments, while, Efficiency, and Reliability show negative sentiments. In addition, based on the results of sentiment analysis, this research also examines topic modeling which is used to see what topics often appear in both applications.